The prevalence and consequences of malnutrition risk in elderly Albanian intensive care unit patients - Shpata, Vjollca (Clin Interv Aging, 2015)
PURPOSE: Many investigators have reported rising numbers of elderly patients admitted to the intensive care units (ICUs). The aim of the study was to estimate the prevalence of malnutrition risk in the ICU by comparing the prevalence of malnutrition between older adults (aged 65 years and above) and adults (aged 18–64 years), and to examine the negative consequences associated with risk of malnutrition in older adults. MATERIALS AND METHODS: A prospective cohort study in the ICU of the University Hospital Center of Tirana, Albania, was conducted. Logistic regression analysis was used to analyze the effect of malnutrition risk on the length of ICU stay, the duration of being on the ventilator, the total complications, the infectious complications, and the mortality. RESULTS: In this study, 963 patients participated, of whom 459 patients (47.7%) were aged ≥65 years. The prevalence of malnutrition risk at the time of ICU admission of the patients aged ≥65 years old was 71.24%. Logistic regression adjusted for confounders showed that malnutrition risk was an independent risk factor of poor clinical outcome for elderly ICU patients, for 1) infections (odds ratio [OR] =4.37; 95% confidence interval [CI]: 2.61–7.31); 2) complications (OR =6.73; 95% CI: 4.26–10.62); 3) mortality (OR =2.68; 95% CI: 1.72–4.18); and 4) ICU length of stay >14 days (OR =5.18, 95% CI: 2.43–11.06). CONCLUSION: Malnutrition risk is highly prevalent among elderly ICU patients, especially among severely ill patients with malignancy admitted to the emergency ward. ICU elderly patients at malnutrition risk will have higher complication and infection rates, longer duration of ICU stay, and increased mortality. Efforts should be made to implement a variety of nutritional care strategies, to change the nutritional practices not only at ward level, but nationally, according to the best clinical practice and recent guidelines.